1997
DOI: 10.1159/000244476
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Maternal Blood Flow on the Placental Transfer of Three Opioids – FentanyI, Alfentanil, Sufentanil

Abstract: The placental transfer of three opioids used in peridural analgesia, fentanyl, alfentanil and sufentanil, and two reference substances, antipyrine and *H2O, was determined ex vivo in the human placental cotyledon system. (1) In the first set of experiments, the infusion rates were constant and fixed at physiological flow rates. Under these conditions, the magnitude of the materno-fetal transfer was in the following order: *H2O = antipyrine = fentanyl > alfentanil > sufentanil. No particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Passive diffusion is limited by physico-chemical properties of substrates. Only unionized low molecular weight substances can transfer by passive diffusion and the rate of transport is enhanced by lipophilicity (Giroux et al, 1997). Facilitated diffusion refers to a process requiring the presence of a carrier substance but does not involve the transfer of energy.…”
Section: Figurementioning
confidence: 99%
“…Passive diffusion is limited by physico-chemical properties of substrates. Only unionized low molecular weight substances can transfer by passive diffusion and the rate of transport is enhanced by lipophilicity (Giroux et al, 1997). Facilitated diffusion refers to a process requiring the presence of a carrier substance but does not involve the transfer of energy.…”
Section: Figurementioning
confidence: 99%
“…Fentanyl, one of the potent systemic opioids used for maternal analgesia during labor, readily crosses the placenta, 1, 2 and may induce adverse effects in the fetus and the neonate. 3 When administered to the neonate, potential adverse effects are respiratory depression, de-saturation episodes, lower heart rate and sleep-state disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…1, 6 Moreover, it has been recently shown that there is a positive correlation between a higher rate of fentanyl clearance after birth, and advanced gestational age and birth weight, whereas in preterm infants the clearance spectrum is very wide mainly because of hepatic immaturity. 7 Therefore, extremely preterm infants are at an increased risk of chest-wall rigidity induced by the placental fentanyl transfer.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, materno-fetal transfer is more rapid and complete for opioids and the lipid-soluble local anesthetics used in obstetrics than for water-soluble substances. These findings emphasize the importance of the lipophilic and hydrophilic characteristics of drugs on placental transfer, especially in the event of fluctuations in maternal flow [88].In several studies the transfer of methadone was investigated using concentrations in the maternal perfusate which were similar to those measured in serum of pregnant women under treatment with the drug. The transfer of methadone and its clearance index was significantly higher in the fetal to maternal than in the maternal to fetal direction with no adverse effects on placental viability and functional parameters, although a substantial fraction of this opiate is retained by the placental tissue [89].…”
mentioning
confidence: 85%